PEMAKNAAN KHALAYAK PENDAKI GUNUNG PADA BERITA KECELAKAAN PENDAKIAN DI MEDIA ONLINE - Razan Fathantra, Ryan; Nur Suryanto Gono, Joyo; Naryoso, Agus (Interaksi Online, 2024)
News is a communication medium that is interesting to study. Through news, the chronology of climbing accidents in Indonesian mountains is described to the public and becomes an interesting topic for research. This study aims to describe and understand the perspectives of mountain climbers on 3 climbing accident news in online media. The three news articles contain detailed chronologies of climbing accidents, two of which resulted in fatalities. This research uses Stuart Hall's reception analysis method to determine the audience's positions of meaning. The study was conducted with 4 informants: 2 novice climbers and 2 experienced climbers. The results show that all four informants agree with the 7 preferred readings that emerge from the three climbing accident news articles. Most informants accept the dominant meanings of the three climbing accident news articles, but in some specific aspects, there are negotiated readings from the informants